Hourglass-shaped grafts are superior to conventional grafts for restoring knee stability and graft force at knee flexion angle of 30° following anterior cruciate ligament reconstruction: A finite element analysis - Wang, Huizhi; Fang, Chaohua; Tao, Mingzhu; Shi, Qinyi; He, Kaixin; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2022)
Background: ACL reconstruction (ACLR) using a generally columnar graft is considered the gold standard for treating ACL ruptures, but such grafts cannot replicate the geometry and mechanical properties of the native ACL. Purpose: To evaluate the effectiveness of an innovative hourglass-shaped graft versus a traditional columnar graft for restoring joint stability and graft force, while avoiding notch impingement following ACLR. Methods: Finite element models of a human knee were developed to simulate ① An intact state, ② ACLR using columnar grafts with different diameters (7.5 - 12 mm in 0.5 mm increments), ③ ACLR using columnar grafts with different Young’s moduli (129.4, 168.0 and 362.2 MPa) and ④ ACLR using hourglass-shaped grafts with different Young’s moduli. The knee model was flexed to 30° and loaded with an anterior tibial load of 103 N, internal tibial moment of 7.5 Nm, and valgus tibial moment of 6.9 Nm. The risk of notch impingement, knee stability and graft forces were compared among the different groups. Results: This study found that columnar grafts could not simultaneously restore knee stability in different degree of freedoms (DOFs) and graft force to a level similar to that of the intact knee. The anterior tibial translation and graft force were restored to a near-normal condition when the internal tibial rotation was over-restrained and valgus tibial rotation was lax. A graft diameter of at least 10 mm was needed to restore knee stability and graft force to physiological levels, but such large grafts were found to be at high risk of notch impingement. In contrast, the hourglass-shaped graft was able to simultaneously restore both knee stability and graft force at knee flexion of 30° while also having a much lower risk of impingement. Conclusions: Under knee flexion angle of 30°, an hourglass-shaped graft was better able to restore joint stability and graft force to a near-physiological level than columnar grafts, while also reducing the risk of notch impingement. Clinical Relevance: This study provide innovative concepts for designing and choosing suitable grafts for ACLR, especially when using allografts or artificial grafts, and thus may improve the clinical outcome of ACLR.